THE EFFECTIVE LEARNING MEDIA FOR EARLY CHILDHOOD IN IMPROVING LIFE SKILLS AT SEKOLAH ALAM MATOA: Media Pembelajaran Efektif Bagi Anak Usia Dini Dalam Meningkatkan Life Skill Di Sekolah Alam Matoa - Ariani, Alya; Muhyidin Nurzaelani, Mohammad; Widyasari, Widyasari (EDUCATE, 2024)
Mastery of life skills needed by young children aims to learn to be independent from an early age, so that they become people who are able to carry out all activities alone without the help of others. The use of media in the learning process is an important component in learning because it can influence students' psychology and make them more motivated in the learning process. This research aims to analyze the need to develop effective learning media in improving the life skills of students at the Alam Matoa School Kindergarten. This research is qualitative research with a survey method. Data collection techniques are interviews and document analysis. Based on the research results, the problems found include: 1)The life skills possessed by students are not yet proficient in several aspects of independence, 2)There is no effective learning media available to improve life skills, and 3)There is no visible habit of students to carry out life skills daily. Based on data analysis, effective learning media is needed to improve life skills by carrying out simple practices directly through busy books. This busy book learning media is able to increase independence, can be used with direct practice and used repeatedly.